2009
DOI: 10.1183/09031936.00092309
|View full text |Cite
|
Sign up to set email alerts
|

Usual interstitial pneumonia in rheumatoid arthritis-associated interstitial lung disease

Abstract: Interstitial lung disease is a common manifestation of rheumatoid arthritis; however, little is known about factors that influence its prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
380
6
22

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(447 citation statements)
references
References 36 publications
18
380
6
22
Order By: Relevance
“…These patterns are commonly found in CTD-ILD, and their presence should raise the suspicion for an underlying autoimmune process [45,46]. A radiologic pattern of UIP is seen in CTD as well ( particularly in rheumatoid arthritis [47]), and as such, patients with a radiologic UIP pattern are not excluded from the IPAF definition. However, UIP was not included as a specific morphologic feature because in a patient with interstitial pneumonia, the presence of a UIP pattern alone does not increase the likelihood of having CTD.…”
Section: Interstitial Pneumonia Patterns Suggested By Thoracic Hrctmentioning
confidence: 99%
“…These patterns are commonly found in CTD-ILD, and their presence should raise the suspicion for an underlying autoimmune process [45,46]. A radiologic pattern of UIP is seen in CTD as well ( particularly in rheumatoid arthritis [47]), and as such, patients with a radiologic UIP pattern are not excluded from the IPAF definition. However, UIP was not included as a specific morphologic feature because in a patient with interstitial pneumonia, the presence of a UIP pattern alone does not increase the likelihood of having CTD.…”
Section: Interstitial Pneumonia Patterns Suggested By Thoracic Hrctmentioning
confidence: 99%
“…Histopathology in these patients can be either UIP or NSIP, with UIP being more common. RA-ILD patients, who have UIP, have a survival similar to that of matched subjects with IPF (Park et al 2007;Kim et al 2010). Data from idiopathic interstitial pneumonia (IIP) population show that HRCT chest can accurately predict the presence of histopathologic UIP pattern in a subset of patients (Hunninghake et al 2003) and several studies in RA-ILD have suggested similar specificity (Assayag et al 2014).…”
Section: Dpld In Ramentioning
confidence: 98%
“…HRCT is widely available, reliable in hands of experienced radiologists, low cost and low risk compared to surgical lung biopsy. Patients with UIP pattern and extensive fibrosis on HRCT should be counseled on their poor prognosis and appropriate patients should be considered for lung transplantation (Kim et al 2010).…”
Section: Dpld In Ramentioning
confidence: 99%
“…Survival in patients with ILD associated with connective tissue disease is better than that of IPF [24]. Studies concerned with the determinants of long-term prognosis are emerging [25]; for example, the pattern on HRCT or the extent of ILD on HRCT are predictive of survival in patients with systemic sclerosis or rheumatoid arthritis, respectively [26,27]. Differentiating IPF from occult or undifferentiated connective tissue disease is a recurring question in clinical care, with frequent therapeutic consequences, especially in patients with a histological pattern of nonspecific interstitial pneumonia.…”
Section: Evolving Phenotypes Of Ildmentioning
confidence: 99%